Chemistry of Biological Processes: An Introduction - Marc Fontecave (Collège de France, 2014)
Life depends on the ability of living organisms to effectively harness the chemical potential of their environment, namely the sun, for energy, and a certain number of molecules which exist on the Earth's surface, such as water, oxygen, carbon dioxide, nitrogen, etc. These molecules need to be activated if benefit is to be derived from them, which requires profound electronic modifications that only metal ions can provide. Truly extraordinary metalloenzymes with highly subtle mechanisms are r...